Conceptualising Centres of Clinical Excellence: A Scoping Review - Elizabeth A Lynch; Jeroen M Hendriks; Natalie Ann Fini; Thoshenthri Kandasamy; Rachel C Stockley; Lemma N Bulto (BMJ Open)
Objectives Centres of clinical excellence (CoCE) are healthcare facilities that provide excellent healthcare. However, despite their increasing prevalence, it is unclear how CoCE are identified and monitored. This paper explores how CoCE has been described in the literature, including its defining characteristics and selection and monitoring processes.Design We conducted a scoping review following Arksey and O’Malley’s framework, enhanced by Levac et al. Additionally, we adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines.Data sources A comprehensive search using MEDLINE Ovid, PubMed, Web of Science, CINAHL and Scopus was conducted to identify relevant literature from January 2010 to June 2022.Eligibility criteria for selecting studies We included published studies and grey literature that described how a CoCE was defined, established, monitored or evaluated.Data extraction and synthesis Two independent reviewers completed the title and abstract screening, reviewed the full texts and extracted data.Results 50 records describing 45 initiatives were included. More than half were published in the USA (n=25, 56%). All but one initiative focused on one clinical condition/population, most commonly cardiovascular disease (n=8, 17%), spinal surgeries (n=4, 9%) and pituitary tumours (n=4, 9%). Most initiatives (n=30, 67%) described a structured process to establish CoCE. The definitions of CoCE were not uniform. Common defining features included the volume of patients treated, medical expertise, a highly skilled multidisciplinary team, high-quality care and excellent patient outcomes. Identification as a CoCE varied from self-identification with no explicit criteria to application and assessment by an approval panel.Conclusion Despite a growing prevalence of CoCE, there are inconsistencies in how CoCE are established, identified, monitored and evaluated. Common (but not uniform) features of CoCE are highly skilled staff, high-quality care delivery and optimal patient outcomes.